What to do with the Problem of the Flesh?: Negotiating Orthodox Jewish Sexual Anxieties - Avishai, Orit (Fieldwork in religion, 2012)
Feminist and queer assessments of religion and sexuality often assume that regulation and affirmation of sexuality are incompatible. This article provides an alternative perspective. The article discusses three orthodox Jewish responses to the "problem of the flesh" - a purported incompatibility of carnality/desire and piety/religiosity: a traditionalist approach that sanctifies sexuality but problematizes desire; a pragmatic stance that desanctifies sexuality; and a reformist approach that affirms sexuality within the logics of Jewish orthodoxy. While these responses may seem inadequate solutions from critical, queer and feminist perspectives, as they are fraught with tradition, heterosexism and sexism, I make a case for a more generous interpretation by contextualizing these responses within orthodox Jewish culture.